At different speeds: Recovering from the Asian crisis ; on the importance of policy complementarities for growth - Bruno Rocha (Asian Development Bank Institute (ADBI), 2007)
This paper begins with a short review and discussion of the literature on policy complementarities and its implications in terms of (sustainable) growth strategies and the possible emergence of a new policymaking paradigm. Thereafter, it analyses the effect on growth of complementarities in structural policies in the specific context of a post-crisis recovery. The application of this framework to the Asian crisis can be regarded as a natural experiment. As the result of computing a complementarity indicator and a reform level indicator adjusted for complementarity for the most affected economies-Indonesia, the Republic of Korea, Malaysia, and Thailand-this study finds that these indicators, for which a comprehensive group of policy areas was considered, are clearly related to higher immediate resilience and to faster recoveries. The results suggest that while augmenting the levels of the so-called orthodox policies is necessary, it is not sufficient to generate high sustainable growth trajectories, as they must be complemented with other policies and evolve in a parallel way.
Keywords: 330; second-best; complementarity; structural reforms; growth; resilience; recovery; Asian crisis; Wirtschaftskrise; Wirtschaftliche Anpassung; Wirtschaftsreform; Wirkungsanalyse; Indonesien; Südkorea; Malaysia; Thailand